EXPERIMENTAL INVESTIGATION OF THE EFFECTS OF PROBIOTIC SUPPLEMENTATION ON OBESITY AND INFLAMMATION IN OBESE RATS - Gül Eda Kılınç; Mehtap Ünlü Sögüt (Rojan GÜMÜŞ, 2017)
TNF-α levels of antiinflammatory and proinflammatory markers were used to investigate effects Obesity is a disease that occurs when body has many endocrine and metabolic functions and fat tissue is higher than normal. There is strong relationship between obesity and inflammation due to production of numerous lipid molecules called adipokines, such as leptin, tumor necrosis factor (TNF-α), interleukins and adiponectin. It was aimed to study obesity and effect on inflammation in experimentally obese animal model study apllied probiotic supplementation. Three different test animal groups were formed. For this purpose; IL-10 and TNF-α on inflammation; leptin levels were used for investigating effect on development of obesity and total cholesterol, HDL and LDL levels from lipid profiles were planned to examine. In obtained serum samples, these parameters were determined by sandwich ELISA technique with commercially available kits. Mean weights at the beginning of study and at the end of 8 weeks were 240,2±9,7 and 283,8±11,0 gr in first, second and third groups; 254,6±16,0 and 307,0±14,5 gr; 330,0±48,6 and 400,5±65,0 gr respectively. At the beginning and end of the probiotic use, weight averages were 288,6±9,9 and 311,8±17,1 gr in first, second and third groups 313.4±17.1 and 339.6±19.7 gr; 412,0±67,7 and 422,0±71,1 gr respectively. When weights were evaluated before and after probiotic use of third group, weight gain was decreased. Although there was no significant difference in HDL, LDL, IL-10 and leptin levels among all group, there was significant difference in total cholesterol and TNF-α values (p<0,05). Compared to first group and second group, there was significant difference in total cholesterol and TNF-α values, in second and third groups there was significant difference in total cholesterol values (p<0,05). As result; probiotics are recognized as living organisms when taken in sufficient quantities, affect health of environment positively, and these beneficial effects are considered to extend to obesity inflammatory diseases. Probiotic supplementation of normal diet may be healthy approach to prevention of various diseases. In order to spread this application to society as whole, it is necessary to increase number of works.